ANALISIS PERTIMBANGAN HUKUM HAKIM PENGADILAN NEGERI TERHADAP PEMBAGIAN HARTA KEKAYAAN BERSAMA DALAM PUTUSAN NOMOR 97/PDT.G/2022/PN.PTK - NIM. A1011201186, ERFANI MELISA SIREGAR (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractDisputes over the division of joint property frequently occur due to the lack of agreement between the parties involved. In a case adjudicated by the Pontianak District Courtunder case number 97/Pdt.G/2022/PN.Ptk, it was found that after the divorce, the Plaintiff and the Defendant had not divided the joint property by legal provisions. Although the Plaintiff had attempted to resolve the matter through deliberation, the Defendant did not respond. Due to concerns that the Defendant might act in bad faith by transferring the property, the Plaintiff eventually filed a lawsuit with the Pontianak District Court to obtain a ruling on the division of the joint property.This study aims to analyze the judicial reasoning behind the court